Wearable Flow: investigation of materiality in the production of contemporary body/artist - Diniz (Universidade Federal do Recôncavo Baiano, Brazil), Carolina de Paula (Revista Brasileira de Estudos da Presença, 2022)
This study deals with the body in relation to the costume within the context of the contemporary performing arts. We aim to analyze how the body relates directly to the elements that are part of it. We examine the specificity of the body in the creative process, which components are organized in a procedural and concomitant way. We problematize the costume in its action as coauthor in the process. The practice called Wearable Flow is presented, focused on the exploration of the materiality based on the relationship between body, movement, and what is worn in the performing production and development of the artist.